2008
DOI: 10.1159/000178025
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Protein C and Antithrombin in the Fetal Lamb: A Model to Predict Human Neonatal Replacement Dosing

Abstract: Background: The preterm infant is at risk for consumptive coagulopathy and thrombosis due to late maturation of coagulation regulatory proteins. Replacement proteins are available, but neonatal pharmacokinetic data are lacking. Objective: The objective was to determine the pharmacokinetic properties of antithrombin (AT) and protein C (PC) in order to provide data for estimating doses in human infants. Methods: A catheterized ovine model was used to determine pharmacokinetic properties of AT and PC, including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…78 Pharmacokinetic studies of ovine antithrombin and protein C showed increased volume of distribution and shortened half-life of both proteins in the fetal lamb compared with the ewe indicating more rapid turnover. 79 Thus, the neonatal hemostasis system exhibits differential effects of regulation of expression, protein kinetics, and impact of maternal conditions.…”
Section: Hemostasis Development In the Fetusmentioning
confidence: 99%
“…78 Pharmacokinetic studies of ovine antithrombin and protein C showed increased volume of distribution and shortened half-life of both proteins in the fetal lamb compared with the ewe indicating more rapid turnover. 79 Thus, the neonatal hemostasis system exhibits differential effects of regulation of expression, protein kinetics, and impact of maternal conditions.…”
Section: Hemostasis Development In the Fetusmentioning
confidence: 99%